Correlation between myoferlin expression and lymph node metastasis in papillary thyroid carcinoma - Ji Min Na; Dong Chul Kim; Dae Hyun Song; Hyo Jung An; Hyun Min Koh; Jeong-Hee Lee; Jong Sil Lee; Jung Wook Yang; Min Hye Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
Background Myoferlin is a multifunctional protein expressed in various normal and cancer cells, with novel oncogenic roles being newly discovered. Recently, correlations have been found between myoferlin expression and unfavorable prognosis in various carcinomas. This study investigated the prognostic role of myoferlin expression in papillary thyroid carcinoma (PTC), specifically that associated with nodal metastasis. Methods We collected clinicopathological data and PTC tissues from 116 patients who had been admitted to Gyeongsang National University Hospital in 2010. Immunohistochemical analysis was performed on surgical specimen-derived tissue microarray blocks. Myoferlin expression was graded, and the relationship between expression level and pathological features of tumors based on the American Joint Committee on Cancer staging system was evaluated. Results Of the 116 patient samples, 100 cases exhibited positive myoferlin expression. Higher grade of myoferlin expression was correlated with lower T category group (p = .010). Presence of lymph node metastasis was determined to be significantly correlated with low-grade myoferlin expression (p = .019), with no significant difference between pN1a and pN1b tumors. Conclusions Our study revealed an adverse correlation between myoferlin expression and pathological features of PTC, evidence of the potential prognostic role of myoferlin in PTC lymph node metastasis.